Efferocytosis-induced prostaglandin E2 production impairs alveolar macrophage effector functions during Streptococcus pneumoniae infection - Salina, Ana C.G. [UNESP]; Souza, Tais P. [UNESP]; Serezani, Carlos H.; Medeiros, Alexandra I. [UNESP] (SAGE Publications, 2017)
Alveolar macrophages (AMs) are multitasking cells that maintain lung homeostasis by clearing apoptotic cells (efferocytosis) and performing antimicrobial effector functions. Different PRRs have been described to be involved in the binding and capture of non-opsonized Streptococcus pneumoniae, such as TLR-2, mannose receptor (MR) and scavenger receptors (SRs). However, the mechanism by which the ingestion of apoptotic cells negatively influences the clearance of non-opsonized S. pneumoniae remains to be determined. In this study, we evaluated whether the prostaglandin E2 (PGE2) produced during efferocytosis by AMs inhibits the ingestion and killing of non-opsonized S. pneumoniae. Resident AMs were pre-treated with an E prostanoid (EP) receptor antagonist, inhibitors of cyclooxygenase and protein kinase A (PKA), incubated with apoptotic Jurkat T cells, and then challenged with S. pneumoniae. Efferocytosis slightly decreased the phagocytosis of S. pneumoniae but greatly inhibited bacterial killing by AMs in a manner dependent on PGE2 production, activation of the EP2-EP4/cAMP/PKA pathway and inhibition of H2O2 production. Our data suggest that the PGE2 produced by AMs during efferocytosis inhibits H2O2 production and impairs the efficient clearance non-opsonized S. pneumoniae by EP2-EP4/cAMP/PKA pathway.
Keywords: alveolar macrophages; apoptotic cells; Efferocytosis; prostaglandin E2; Streptococcus pneumoniae